2022
DOI: 10.1002/app.53471
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic flame‐retardant effect of modified hydrotalcite and expandable graphite for silicone rubber foam

Abstract: Silica gel‐coated hydrotalcite (LDHs) flame retardants (SiLDHs‐Ce) are prepared by the sol–gel method. The synergistic effect of SiLDHs‐Ce and expandable graphite (EG) on the silicone rubber foam (SRF) is studied through limiting oxygen index (LOI), Cone Calorimeter Test (CC), thermogravimetric infrared spectrometer (TG‐IR), and scanning electron microscopy. The results show that SiLDHs‐Ce and EG can improve the flame retardant properties of the SRF materials. The LOI value of the SRF material can reach 40.1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Liu et al synthesized silica-coated hydrotalc (SiLDHs-Ce) using the sol–gel method and integrated both expandable graphite (EG) and SiLDHs-Ce into silicone rubber foam (SRF) to enhance its flame-retardant efficiency . Their findings indicated that SiLDHs-Ce and EG substantially improved the flame-retardant properties of SRF.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al synthesized silica-coated hydrotalc (SiLDHs-Ce) using the sol–gel method and integrated both expandable graphite (EG) and SiLDHs-Ce into silicone rubber foam (SRF) to enhance its flame-retardant efficiency . Their findings indicated that SiLDHs-Ce and EG substantially improved the flame-retardant properties of SRF.…”
Section: Introductionmentioning
confidence: 99%
“…Silicone rubber foam (SiFs) is a high-performance and functional polymeric elastomer composed of Si-O-Si bonds as the main chain [1][2][3]. SiFs not only has electrical insulation, non-toxicity, durability in various weather conditions, and chemical stability, but also has the characteristics of lightweight, soundproof, and sound shock-absorbing [3,4], so it is widely used in aerospace, transportation, medicine, national defense, architecture, and other fields [5][6][7]. However, SiFs contains a large number of hydrocarbon groups, it can burn and release vast quantities of smoke when encountering a flame, which limits its promotion and application in high flame-retardant requirement fields [8,9].…”
Section: Introductionmentioning
confidence: 99%